Mesozooplankton biomass and secondary production in a temperate estuary: effects of processes operating at different time scales - Mendes, Dina Amanda (2014)
Dissertação de Mestrado em Ecologia Aplicada, apresentada ao Departamento de Ciências da Vida da Faculdade de Ciências e Tecnologia da Universidade de Coimbra.